A Brief Overview of Gbagyi Beyekpe (Education) and Imperialism in Minna 1928 – 1960 - Idris, Abubakar Zakari; Umar, Alhaji Bako (Current Approaches in Science and Technology Research Vol. 3, 2021)
The present chapter discussed the Gbagyi Beyekpe (education) and imperialism in Minna, 1928-1960. The contact of the Gbagyi in Minna with imperialism dates back to the early part of the twentieth century. As a result of the Gbagyi’s interaction with imperial power, a new system of knowledge substituted the Gbagyi’s Beyekpe (education), which was a process of educating the children and every individual for happy and productive living and to create the Gbagyi individual who will be honest, responsible, skilled, cooperative, and adhere to the social order of the day.This new order which was explicitly designed to restructure the social pattern of the Gbagyi and his society began in 1928 and by 1960 had replaced the Gbagyi Beyekpe (education). According to the study, this development ushered in the dependency syndrome that characterised Gbagyi modernity and continues to obstruct Gbagyi and his Minna society’s evolution. The paper illustrated the influence of this alien knowledge system on the Gbagyi in Minna and argued for a redefinition of the Gbagyi knowledge system that is distinct from the western educational tradition, which stresses superiority as a measure of educational attainment holistically.